The effects of pharmacological accommodation and cycloplegia on axial length and choroidal thickness - Bahar,Alperen (2021)
ABSTRACT Purpose: To investigate the effects of pharmacological accommodation and cycloplegia on ocular measurements. Methods: Thirty-three healthy subjects [mean (±SD) age, 32.97 (±5.21) years] volunteered to participate in the study. Measurement of the axial length, macular and choroidal thickness, refractive error, and corneal topography, as well as anterior segment imaging, were performed. After these procedures, pharmacological accommodation was induced by applying pilocarpine eye drops (pilocarpine hydrochloride 2%), and the measurements were repeated. The measurements were repeated again after full cycloplegia was induced using cyclopentolate eye drops (cyclopentolate hydrochloride 1%). The correlations between the measurements were evaluated. Results: A significant increase in subfoveal choroidal thickness after applying 2% pilocarpine was identified (without the drops, 319.36 ± 90.08 µm; with pilocarpine instillation, 341.60 ± 99.19 µm; with cyclopentolate instillation, 318.36 ± 103.0 µm; p<0.001). A significant increase in the axial length was also detected (without the drops, 23.26 ± 0.83 mm; with pilocarpine instillation, 23.29 ± 0.84 mm; with cyclopentolate instillation, 23.27 ± 0.84 mm; p=0.003). Comparing pharmacological accommodation and cycloplegia revealed a significant difference in central macular thickness (with pilocarpine instillation, 262.27 ± 19.34 µm; with cyclopentolate instillation, 265.93 ± 17.91 µm; p=0.016). Pilocarpine-related miosis (p<0.001) and myopic shift (p<0.001) were more severe in blue eyes vs. brown eyes. Conclusion: Pharmacological accommodation may change ocular measurements, such as choroidal thickness and axial length. This condition should be considered when performing ocular measurements, such as intraocular lens power calculations.